Association between dengue and pediatric AUF: A study from Chennai and Kochi, South India - Sara Chandy; Divya Narayanan; Anand Manoharan; Vignesh Moorthy; Gowridevi Vankayala; Hemalatha Ramachandran; Rohitha Chandra (Clinical Epidemiology and Global Health)
Background: Acute Undifferentiated Fever (AUF) is a common clinical presentation at hospitals in tropical and subtropical countries. Both children and adults present with this clinical condition which is difficult to diagnose clinically and has infectious and non-infectious causes. Early and accurate diagnosis of AUF requires good diagnostic tools. Dengue remains the most common infectious cause of AUF in India, followed by scrub typhus. All the four dengue serotypes (DEN1, DEN2, DEN3 and DEN4) cause disease in children and adults with clinical presentation ranging from febrile illness to severe dengue manifested as shock and multi-organ failure. Methods: This study, done in South India, explores the dengue burden in AUF cases, dominant serotypes, and their clinical manifestations. Results: Our study indicates that from 2022 to 2023, DEN2 remained the most common circulating serotype closely followed by DEN3. DEN3 is emerging fast and likely to become the most predominant serotype in Chennai. Conclusion: Multiplex real time PCR is currently accepted as an affordable and sensitive tool for diagnosis of infectious causes of AUF. Serotype surveillance is important for controlling outbreaks and for clinical management of pediatric patients.